If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15 + -6x = 18 + -5x Solving 15 + -6x = 18 + -5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5x' to each side of the equation. 15 + -6x + 5x = 18 + -5x + 5x Combine like terms: -6x + 5x = -1x 15 + -1x = 18 + -5x + 5x Combine like terms: -5x + 5x = 0 15 + -1x = 18 + 0 15 + -1x = 18 Add '-15' to each side of the equation. 15 + -15 + -1x = 18 + -15 Combine like terms: 15 + -15 = 0 0 + -1x = 18 + -15 -1x = 18 + -15 Combine like terms: 18 + -15 = 3 -1x = 3 Divide each side by '-1'. x = -3 Simplifying x = -3
| 4x^2-20x=24 | | 5m+3n-2m+10n= | | 4x^2(x+1)-9(x+1)=0 | | 49v^2-28vu+4u^2=0 | | 2=-4.9(2)+19.6(2)+1 | | 125-7x=11x+19 | | 0=x^2-24+c | | 3(x-4)-(6x+3)=3(4x+1) | | 19/10=c/23 | | x+2-3x-4+5x-6+7x-8=9x+10-11x+12 | | 26-x=2(4x-5) | | x^2+2x+12(x^2+2x)=7 | | 74x=24 | | 2w^5+24w^4+72W^3=0factor | | 4v^2+15+15=0 | | 4x=94 | | -7.9-3y-5.1-y=3y-6.3 | | (-x/20-5/2)^2 | | 2w+24w+72W^3=0 | | 2w+24w^4+72W^3=0 | | 2w^4+24w^4+72W^3=0 | | 3/4(x+8)=18 | | (3a+2b)(5a+b)=0 | | -31=-4y+9 | | 2w^5+24w^4+72W^3=0 | | 8x^3=-26x | | -2-x=3(3x-6) | | -14x+2y=8 | | (2x-3)(4x+7)=0 | | 2(x-4)-(4x+6)=4(5x+4) | | 4x-2=32x+19 | | -v^2+v+12=0 |